Pengaruh Permainan Tradisional Galasin Terhadap Kelincahan Pada Siswa Kelas VII MTs Mathla’ul Anwar Sabajaya Karawang - Hana Nuryana; Muhammad Mury Syafei; Irfan Zinat Achmad (Universitas Singaperbangsa, 2021)
This study aims to determine how much influence the traditional galasin game has on agility in class VII students of MTs Mathlaul Anwar Sabajaya Karawang. The background in this problem is the lack of students' agility during Physical Education learning, so the writer in this case will examine how the influence of traditional galasin games on agility using quantitative approaches and quasi-experimental research methods (Quasi Experimental Research). The design used was the pretest-posttest control group design. The population of all students in class VI, totaling 62 people, was divided into two classes, namely class VII.A and class VII.B, each of which consisted of 31 people. However, at the time of the research there was one student from class VII.A and VII.B who was sick, so the sample size was 30 people. Because the population is below 100 people in a homogeneous state because they come from the same class strata, the entire population is sampled. This data collection uses tests and measurements. The data analysis technique used was the Normality Test, Homogeneity Test, Two-Mean Difference Test and Gain Data Analysis. The results obtained from hypothesis testing with the two mean similarity test at the level of significance a = 0.05 obtained P-Value = 0.000 thus H0 is rejected, meaning that the increase in student agility in traditional galasin games using zig-zag running training is higher than student agility in traditional galasin games by not using zig-zag running training. This can be seen from the results of the mean value of student agility (Gain) with the experimental class mean score of 21.53 and the control class mean value of 12.20. The conclusion of this study in general is that the traditional galasin game can improve the agility of grade VII students of MTs Math'lau Anwar Sabajaya Karawang.